Human Right Impact Assessment (HRIA): The Importance Of Community Involvement In International Agreement - Anita Amaliyah; Ika Riswanti Putranti (JURNAL ILMU SOSIAL, 2020)
In the growing international agreements as a consequence of Indonesia’s wider participation in the global community, the existence of free market harms the domestic industrial sector, especially to the community. The number of treaties which have been ratified by the government considered as incomparable to the losses incurred, particularly to the possibility of human rights violations of information dysfunction, and the lack of public participation as well as evaluation functions. This study uses a descriptive qualitative approach where data is obtained from primary and secondary data. The purpose of this study is to find out the conceptual and practical considerations faced in the possibility of violations of human rights. Moreover, the article also addresses the form of diplomacy carried out by the public regarding several government policies in the Free Trade Agreement and its relations to human rights. The study suggests that the government must guarantee human rights by involving affected communities as a form of collective understanding. Furthermore, the government must also monitor, evaluate, assess, as well as strengthen the communication from various stakeholders to eliminate the hidden costs that can harm the community.